An Analysis of the Third Year Students’ Difficulties in Writing Argumentative Essay at English Department of FKIP Bung Hatta University - Retno Yulansari (Vivid: Journal of Language and Literature, 2019)
This research aimed to find out students' difficulties in writing an argumentative essay. The research used descriptive method; the population was the third year students of the English department, FKIP Bung Hatta University Padang. They were divided into four classes, A, B, C and D. Sample of this research was class B, and the size of the sample was 35 students.  The writer used the cluster random sampling technique to get a representative sample. The research result showed that that is 21(60%) students have difficulties in writing an argumentative essay and the result of the writing test. Specifically, from data analysis of writing task showed that 21(60%) students had difficulties in organization of idea, 22(62.85%) students in grammar, 20 (57.14%) students vocabulary, 21 (60%) students in using transition signal, and 21(60%) students in mechanics.